2011
DOI: 10.1111/j.1750-3841.2011.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Shelf‐Life Limiting Factor of High Hydrostatic Pressure Processed Avocado Paste

Abstract: At present, HHP is the most effective commercial nonthermal technology to process avocado paste when compared to thermal and chemical alternatives. HHP-treated avocado paste is a microbiologically stable food for a period of at least 45 d stored under refrigeration. However, previous published work indicated that consumers rejected the product after approximately 19 d of storage due to sensory changes. This manuscript presents a sensory study that permitted the identification of the critical sensory descriptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 20 publications
4
10
0
1
Order By: Relevance
“…In studies involving the survival analysis, values of 10%, 25% and 50% as the percentages of consumer rejection have been considered (Gambarro et al, 2006;Hough et al, 2003;Jacobo-Velázquez and Hernández-Brenes, 2010). In the present study, values of 10% and 25% were taken into consideration, since high rejection levels could result in economic losses for the oligofructose supplier, which would be prohibitive.…”
Section: Survival Analysis Methodologymentioning
confidence: 99%
“…In studies involving the survival analysis, values of 10%, 25% and 50% as the percentages of consumer rejection have been considered (Gambarro et al, 2006;Hough et al, 2003;Jacobo-Velázquez and Hernández-Brenes, 2010). In the present study, values of 10% and 25% were taken into consideration, since high rejection levels could result in economic losses for the oligofructose supplier, which would be prohibitive.…”
Section: Survival Analysis Methodologymentioning
confidence: 99%
“…Lambert and others (1999) studied the impact of HP treatments (200 to 800 MPa/20 °C/20 min) on the aromatic volatile profile of strawberry purée and they found that pressure treatments of 200 and 500 MPa did not affect the aroma profile, while a significant change was observed in the HP‐treated (800 MPa) strawberry purée compared to untreated sample by inducing the synthesis of new compounds. In a study performed by Jacobo‐Velázquez and Hernández‐Brenes (2011), they used a trained panel and a consumer panel to determine the sensory shelf‐life‐limiting factor of HP‐treated (600 MPa/23 °C/3 min) avocado paste during 45 d storage at 4 °C. In this study, the trained panel identified sour and rancid favors as the main sensory descriptors (critical descriptors) that are able to discriminate stored from untreated samples.…”
Section: Fruit and Vegetable Purées/pastesmentioning
confidence: 99%
“…Rancid and other off‐note characteristics from lipid degradation in food often have low threshold values and are easily perceived by human even at low concentration (Jacobsen, ; Skibsted, Mikkelsen, & Bertelsen, ; W'sowicz et al., ). Rancidity‐related sensory attributes also have been used as critical descriptors for shelf life estimation for several products, such as extruded pet food (Chanadang et al., ), avocado paste (Jacobo‐Velázquez & Hernández‐Brenes, ), and spray‐dried fish oil powder (Keogh et al., ). For this study, the end of shelf life of all FBFs was determined as the last storage time that did not show a significant increase ( P ≤ 0.05) in rancid and painty characteristics.…”
Section: Resultsmentioning
confidence: 99%